High Activity Hydrogen Evolution Catalysis by Uniquely Designed Amorphous/Metal Interface of Core–shell Phosphosulfide/N‐Doped CNTs. Issue 13 (22nd January 2018) - Li, Dong Jun; Kang, Joonhee; Lee, Ho Jin; Choi, Dong Sung; Koo, Sung Hwan; Han, Byungchan; Kim, Sang Ouk
Abstract: A cost effective hydrogen evolution reaction (HER) catalyst that does not use precious metallic elements is a crucial demand for environment‐benign energy production. The family of earth‐abundant transition metal compounds of nitrides, carbides, chalcogenides, and phosphides is one of the promising candidates for such a purpose, particularly in acidic conditions. However, its catalytic performance is still needed to be enhanced through novel material designs and crystalline engineering. Herein, a chemically and electronically coupled transition metal phosphosulfide/N‐doped carbon nanotubes (NCNT) hybrid electrocatalyst is fabricated via a two‐step synthesis. The uniquely designed synthesis leads to the material morphology featuring a core–shell structure, in which the crystalline metal phosphide core is surrounded by an amorphous phosphosulfide nanoshell. Notably, due to the favorable modification of chemical composition and surface properties, core–shell CoP@PS/NCNT exhibits the noticeable HER activity of approximately −80 mV @ −10 mA cm −2 with excellent durability, which is one of the highest active nonnoble metal electrocatalysts ever reported thus far. Abstract : A chemically and electronically coupled transition metal phosphosulfide/N‐doped carbon nanotubes (NCNT) hybrid electrocatalyst is fabricated via a two‐step synthesis. The uniquely designed synthesis leads to the material morphology featuring a core–shell structure, where the crystalline metal phosphide core is surrounded by an amorphous phosphosulfide nanoshell. Notably, due to the favorable modification of the chemical composition and surface properties, core–shell CoP@PS/NCNT exhibits remarkable hydrogen evolution reaction activity.